An Investigation of School Improvement Recognition Towards Madrasah’s Teachers in East Java - Ali Mustofa; Mukhlas Samani; Soedjarwo (IJORER : International Journal of Recent Educational Research, 2021)
This study aimed at investigating the relationship between school improvement and demographic variables such as age, gender, length of teaching, teacher’s employment status and educational background. Involving 400 participants of Madrasah Tsanawiyah’s (Islamic junior high schools) teachers in East Java and using school improvement scale, this study found that the higher teacher’s educational qualification is, the better the performance shown, which subsequently had consequences for school improvement in assisting students’ achievement. Likewise, the length of teaching and teachers’ employment status were found bringing influence on school improvement although their correlation directions vary. Meanwhile, gender and age are not related to school improvement. This study suggested teachers’ professional development to enable assistance for students’ success and eventually lead to school improvement.